2013
DOI: 10.1002/bjs.9337
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting invasion in patients with a preoperative diagnosis of ductal carcinoma in situ of the breast

Abstract: Upstaging to invasive cancer in women with a preoperative diagnosis of DCIS is common. A nomogram based on the five most significant factors related to upstaging accurately predicted invasive cancer. This nomogram may be useful when deciding whether to pursue axillary staging with sentinel lymph node biopsy in patients with DCIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 35 publications
8
49
1
Order By: Relevance
“…Two previous studies found a correlation between ER-negative tumors and upstaging from DCIS to invasive cancer. 29,30 High grade and ER negativity were predictive of SLNB with lumpectomy in our cohort. Additionally, 30 % of patients with ER-negative disease alone and 25 % of patients with grade 3 disease alone underwent SLNB.…”
Section: Discussionmentioning
confidence: 88%
“…Two previous studies found a correlation between ER-negative tumors and upstaging from DCIS to invasive cancer. 29,30 High grade and ER negativity were predictive of SLNB with lumpectomy in our cohort. Additionally, 30 % of patients with ER-negative disease alone and 25 % of patients with grade 3 disease alone underwent SLNB.…”
Section: Discussionmentioning
confidence: 88%
“…A meta‐analysis reported by Brennan M E et al, which included 7350 cases of DCIS diagnosed by CNB, showed that tumor size was one of the strongest independent predictors of underestimation . In numerous previous studies, large tumor size, palpable lump, and number of lesions were associated with the risk of upstaging . Other factors, such as nuclear grade, comedo necrosis, sclerosing adenosis, and CNB method, were also correlated with upstaging .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have described rates of LN metastasis in patients with preoperatively diagnosed DCIS ranging from 2.53% to 6.8% . A meta‐analysis showed the rate to be 7.4% .…”
Section: Discussionmentioning
confidence: 99%